The ubiquitin proteasome system in Huntington's disease and the spinocerebellar ataxias - Davies, Janet E (BioMed Central, 2007)
Huntington's disease and several of the spinocerebellar ataxias are caused by the abnormal expansion of a CAG repeat within the coding region of the disease gene. This results in the production of a mutant protein with an abnormally expanded polyglutamine tract. Although these disorders have a clear monogenic cause, each polyglutamine expansion mutation is likely to cause the dysfunction of many pathways and processes within the cell. It has been proposed that the ubiquitin proteasome system is impaired in polyglutamine expansion disorders and that this contributes to pathology. However, this is controversial with some groups demonstrating decreased proteasome activity in polyglutamine expansion disorders, some showing no change in activity and others demonstrating an increase in proteasome activity. It remains unknown whether the ubiquitin proteasome system is a feasible therapeutic target in these disorders. Here we review the conflicting results obtained from different assays performed in a variety of different systems. Publication history: Republished from Current BioData's Targeted Proteins database (TPdb; ).